(untitled) - Primrose, Sandy (Boston, 2001)
Principles of Gene Manipulation provides an excellent introduction to the area of genetic engineering of plants, animals and microbes for advanced level undergraduates with a basic understanding of genetics. This classic textbook has been substantially updated and revised to reflect the rapid advances that have been made in the core technologies in the seven years since the last edition
Keywords: Genetic engineering,Kỹ thuật di truyền